Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja Pegawai Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean B Medan - Amrina Amrina; Lidia Yunita (Institute of Computer Science (IOCS), 2018)
This study aims to determine the effect of occupational safety and health of work productivity in the Office of Supervision of Customs and Excise type of customs B Medan. This research uses multiple regression analysis method. The population in this study were 121 employees and the sample used was 121 respondents using saturated sampling techniques. The results of this study indicate that there is a significant influence between work safety on work productivity partially by 0.569, and the results of the study also show a significant effect between occupational health on work productivity of 0.130. The results of this study also indicate that there is a significant influence between occupational safety and health on the work productivity of employees at the Office of Customs and Excise Customs and Excise Type Services in Medan by 42.4% simultaneously or simultaneously. This is consistent with the results of an analysis of 121 employees as a study sample obtained a coefficient of determination (R Square) of 0.424 while the remaining 57.6% was influenced by other factors not examined in this study.